2008
DOI: 10.5194/acp-8-1559-2008
|View full text |Cite
|
Sign up to set email alerts
|

The time evolution of aerosol composition over the Mexico City plateau

Abstract: Abstract. The time evolution of aerosol concentration and chemical composition in a megacity urban plume was determined based on 8 flights of the DOE G-1 aircraft in and downwind of Mexico City during the March 2006 MILAGRO field campaign. A series of selection criteria are imposed to eliminate data points with non-urban emission influences. Biomass burning has urban and non-urban sources that are distinguished on the basis of CH3CN and CO. In order to account for dilution in the urban plume, aerosol concentra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
215
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(252 citation statements)
references
References 58 publications
33
215
4
Order By: Relevance
“…Tai, are much lower than the values at Miyun, predicted by a model to be 0.4-0.7 . Our range is even lower than that of the NO x / NO y ratio reported by Kleinman et al (2008) over the Mexico City plateau of between 0.11 and 0.83. From these findings, it was concluded that air at Mt.…”
Section: Overview Of Mtx200findingscontrasting
confidence: 49%
See 1 more Smart Citation
“…Tai, are much lower than the values at Miyun, predicted by a model to be 0.4-0.7 . Our range is even lower than that of the NO x / NO y ratio reported by Kleinman et al (2008) over the Mexico City plateau of between 0.11 and 0.83. From these findings, it was concluded that air at Mt.…”
Section: Overview Of Mtx200findingscontrasting
confidence: 49%
“…Tai, around 50 ppbv ppbv −1 , shown as the slope of Fig. 4a, is 1.4 times that at Lin'an (30-40, Wang et al, 2002, about twice that at Changping (20-30, T. and in a plume from Mexico City (20.6, Kleinman et al, 2008), and five or more times that in US vehicular emissions (6-10, Parrish et al, 2002;Parrish, 2006). The large CO / NO y ratio at Mt.…”
Section: Overview Of Mtx200findingsmentioning
confidence: 99%
“…The higher levels of f 44 and absence of a trend with f 60 in the "downwind" plume indicate OA is more heavily oxidised than in the fresher "source" plumes. This contrast in oxygenation is linked to other changes between plumes, including apparent photochemical age, which in this instance is represented by the −log(NO x / NO y ) ratio (Kleinman et al, 2008;DeCarlo et al, 2008). Levels of the ratio are significantly elevated in the "downwind" plume from B626 (Fig.…”
Section: Tracer Evolution During Bortasmentioning
confidence: 97%
“…-Three compact Time-of-Flight Aerosol Mass Spectrometers (C-ToF-AMS) Kleinman et al, 2008;Herndon et al, 2008;de Gouw et al, 2009). …”
Section: Instruments Deployed To Mexico City For the First Timementioning
confidence: 99%